Prevention of malignant neoplasms - D. G. Zaridze; D. M. Maksimovich (Успехи молекулярной онкологии)
Research in causation of cancer is an important part of cancer research in general and is an essential prerequisite for cancer prevention. The effective primary prevention is not visible without evidence based knowledge in the causation of cancer in humans.There is sufficient evidence that certain life style and environment factors cause cancer in humans. These factors include: smoking and other types of tobacco consumption, overweight and obesity, lack of physical activity, diet rich in processed meat and poor in vegetables and fruits, certain types of viral and bacterial infection, ultraviolet radiation, ionizing radiation, ambient air pollution, carcinogens at workplace, exogenous hormones.Cancer mortality is decreasing in majority of developed countries, including Russia. This mortality trend is mostly due to decrease in incidence and death rates of lung and other smoking related cancers and is caused by decline in smoking prevalence and change in tar content of cigarette smoke.In Russia trend in mortality from all cancers is as well determined by decrease in incidence and mortality from gastric cancer, which is due to decline in prevalence of Helicobacter pylori infection and improvement of diet, increase in consumption of fruits and vegetables. Thus the decline in cancer mortality is mostly the result of primary prevention which is the most effective avenue of cancer control.